Presence of supernumerary pieces within the nasopalatine duct - Fernandez Siguencia, María José (2025)
The supernumerary teeth (mesiodens), located between the upper incisors, are often extracted for aesthetic or functional reasons. During their extraction, certain complications must be considered. One such complication is the proximity to the nasopalatine canal, where contact with the vascular-nervous bundle can lead to sensory alterations and other complications. Objectives: To evaluate the presence of supernumerary teeth within the nasopalatine canal using cone beam computed tomography (CBCT) scans conducted at the INNOVA 3D Radiological Center. Materials and Methods: A total of 2,805 CBCT images taken in 2023 were reviewed. Of these, 74 images presented supernumerary teeth in the anterosuperior region. After applying exclusion criteria, a sample of 50 tomograms was selected for analysis. Results: Among the 50 tomograms reviewed, 10 (20%) showed supernumerary teeth located within the nasopalatine canal, while 40 (80%) were located outside or near the canal. Conclusions: Supernumerary teeth (mesiodens) were found within the nasopalatine canal in 20% of the tomograms examined. The remaining cases showed the teeth located at a distance or in close proximity to the canal. This highlights the importance of accurately identifying the location of the nasopalatine canal during dental procedures to minimize the risk of sensory alterations and other complications for the patient.